Diagnosis and multidisciplinary management of bladder endometriosis: A case report - Albinagorta Olórtegui, Roberto (2021)
Bladder endometriosis is a rare medical entity, diagnosed by clinical and imaging procedures. Transvaginal ultrasound is the first line technique for diagnosis. The treatment is laparoscopic, with good results. We present the case of a patient with this pathology, with multidisciplinary surgical approach and satisfactory evolution in the control of the disease.